A Multicenter Study for Establishing Reference Intervals of Serum GDF-15 Levels Based on the Chinese Population - Chen K; Fan X; Wu J; Chen S; Yang J; Shen L; Liu Z; Yuan H (Journal of Inflammation Research)
Ke Chen,1 Xuesong Fan,1,2 Junyi Wu,1 Siyu Chen,1 Jiashu Yang,1 Linlin Shen,1 Zihan Liu,1 Hui Yuan1 1Department of Clinical Laboratory, Beijing Anzhen Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Neurological Surgery, Feinberg School of Medicine, Northwestern University, Chicago, IL, USACorrespondence: Hui Yuan, Department of Clinical Laboratory, Beijing Anzhen Hospital, Capital Medical University, Anzhen Road No. 2, Chaoyang District, Beijing, 100029, People’s Republic of China, Email 18911662931@189.cnPurpose: Growth differentiation factor 15 (GDF-15) is a stress-responsive cytokine mostly linked to pathological conditions including inflammation, myocardial ischemia, and cancer. We aimed to establish reference intervals (RIs) for GDF-15 in a large, multicenter cohort of apparently healthy Chinese individuals.Patients and Methods: Adopting unified and stringent criteria, 8,488 eligible subjects from six representative cities in China were enrolled. Serum GDF-15 concentrations were measured with the Maccura Biotechnology i3000 automatic chemiluminescence analyzer and its corresponding reagents. Outliers were identified using the Tukey’s test. To determine the need for partitioning by age and sex, we conducted a two-level nested analysis of variance (ANOVA), considering an standard deviation ratio (SDR) > 0.3 as indicative of notable subgroup differences. The 2.5th and 97.5th percentiles of the RIs were established using non-parametric statistical methods, with 90% confidence interval.Results: A total of 7,764 participants were included in the data analysis, with 724 outliers excluded. GDF-15 levels displayed a skewed distribution as confirmed by the Kolmogorov–Smirnov test. GDF-15 levels increased with age (All P < 0.001) and were higher in males than in females (all P